Electrical injury of external genitalia and reconstruction with gracilis muscle flap - Jyoshid R Balan (Wolters Kluwer Medknow Publications, 2016)
The high-voltage electrical injury is not uncommon, but the involvement of the genitalia and the perineum is rare. Our patient is a 29-year-old female with electrical injury from a high-tension wire and had injury to the perineum, genitalia, and lower limbs with negligible involvement of the upper limbs. There was a loss of the lower half of the labia majora and she had a tissue defect on the left side of the perineum. The reconstruction was performed with the use of pedicled gracilis flap with a good outcome.